2013
DOI: 10.1042/bj20121880
|View full text |Cite
|
Sign up to set email alerts
|

Proteolytic activation of prochemerin by kallikrein 7 breaks an ionic linkage and results in C-terminal rearrangement

Abstract: The excessive accumulation of adipose tissue in obesity is associated with multiple inflammatory dermatological diseases. Chemerin, a chemoattractant adipokine, dependent on proteolytical activation, is highly expressed in skin. Different proteases have been reported to activate prochemerin, but none is inherently expressed in human skin. In the present study, we identified a tissue-specific protease and investigated the underlying mechanism of activation at the molecular level. We characterized human KLK7 (ka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
66
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 47 publications
(67 citation statements)
references
References 53 publications
0
66
0
Order By: Relevance
“…With this information, chemerin was hypothesized to be linked to psoriasis through pDCs, which was later supported by data showing increased expression in early lesions, especially in fibroblasts [54]. The association of high chemerin levels with psoriatic lesions has been further supported [55] with some expanding upon the method with which chemerin becomes active in the human skin [56]. This trend of elevated chemerin in epithelial lesions holds true for both Crohn's disease and ulcerative colitis [57] so it is possible that at the discovery of chemerin, scientists mistook prochemerin for the active form.…”
Section: - Pathophysiologymentioning
confidence: 93%
“…With this information, chemerin was hypothesized to be linked to psoriasis through pDCs, which was later supported by data showing increased expression in early lesions, especially in fibroblasts [54]. The association of high chemerin levels with psoriatic lesions has been further supported [55] with some expanding upon the method with which chemerin becomes active in the human skin [56]. This trend of elevated chemerin in epithelial lesions holds true for both Crohn's disease and ulcerative colitis [57] so it is possible that at the discovery of chemerin, scientists mistook prochemerin for the active form.…”
Section: - Pathophysiologymentioning
confidence: 93%
“…Additional highly expressed genes that were skin enriched were related to melanin production, including melan-A (MLANA), tyrosinase (TYR) and dopachrome tautomerase (DCT). Also in the list of genes enriched in skin were less-well characterized genes, including SERPINA12, which was earlier shown to be linked to the inhibition of the kalkrein-related peptidase, KLK7, in the development of psoriasis (Schultz et al 2013), and interleukin IL37, which was shown to be associated to atopic dermatitis (Kimura et al 2013). The most highly expressed gene in the skin enriched group was the poorly characterized C1orf68 gene, which encodes for the skinspecific protein 32 (synonyms: LEP7, xp32) located within the epidermal differentiation complex together with other skin-specific genes, including the late cornified envelope proteins (Toulza et al 2007;Zhao and Elder 1997).…”
Section: Classification Of Genes Expressed In Skinmentioning
confidence: 99%
“…In endothelial and vascular smooth muscle cells, multiple studies demonstrated anti-apoptotic (8), anti-inflammatory (9), and anti-migratory (10) effects of vaspin, suggesting a protective role in the pathogenesis of atherosclerosis. In skin, vaspin expression by keratinocytes suppresses the expression and release of inflammatory cytokines by immune cells (11) and possibly regulates the activation of proinflammatory cytokines, such as chemerin, via KLK7 (12). Whereas vaspin-mediated improvement of glucose tolerance and reduction of food intake were found to be dependent on protease inhibition (4,13), anti-inflammatory effects in the liver have been linked to interaction with a membrane-associated endoplasmic reticulum chaperone protein (5).…”
mentioning
confidence: 99%